2013
DOI: 10.5574/ijose.2012.3.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mooring System Design of Floating Offshore Wind Turbine in Jeju Offshore Area

Abstract: This paper presents a mooring design procedure for a floating offshore wind turbine. Offshore environmental data for Jeju are taken from KHOA (Korea Hydrographic and Oceanographic Administration) and used for the environmental conditions in numerical analyses. A semi-submersible-type floating wind system with a 5-MWclass wind turbine studied by the DeepCwind Consortium is applied. Catenary mooring with a studless chain is chosen as the mooring system. Design deliverables such as the nominal sizes of chain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This paper follows the design procedure proposed by Kim et al (2013) [27]. The overall design flowchart of this study is shown in Figure 6.…”
Section: Methodsmentioning
confidence: 99%
“…This paper follows the design procedure proposed by Kim et al (2013) [27]. The overall design flowchart of this study is shown in Figure 6.…”
Section: Methodsmentioning
confidence: 99%
“…The 120-degree interval mooring line configuration is shown in Figure 5. To determine the initial length, the equation for the catenary is applied, and t load of chain grade R3 is selected to determine the maximum tension according rules [20]. The initial mooring lines configuration shown in Table 4 is derived from ton's guidance and iterative design using the methodology outlined in Connolly [32,33].…”
Section: Initial Mooring Designmentioning
confidence: 99%
“…Hence, the laid length is adjusted to the anchor uplift force from being greater than the anchor gravity when enviro loads are applied. The anchor uplift force is generally stipulated not to be grea To determine the initial length, the equation for the catenary is applied, and the proof load of chain grade R3 is selected to determine the maximum tension according to DNV rules [20]. The initial mooring lines configuration shown in Table 4 is derived from Hazelton's guidance and iterative design using the methodology outlined in Connolly and Hall [32,33].…”
Section: Initial Mooring Designmentioning
confidence: 99%
See 1 more Smart Citation